The inefficiency of Reuters foreign exchange quotes - Martens, Martin; Kofman, Paul (Journal of Banking & Finance, 1998)
Reuters foreign exchange (FXFX) page is the world wide predominant information source to foreign exchange traders. In this study we compare the indicative spot exchange rate quotes from Reuters with their matching futures exchange rates from the Chicago Mercantile Exchange. We find that the indicative quotes on Reuters FXFX page are inefficient and could be improved by incorporating information from the futures market. This casts doubt on the way banks determine these quotes, as well as on the informational content of these quotes as an indicator of the current exchange rate.